Electro-optical properties characterization of fish type III antifreeze protein - Salvay, Andrés Gerardo (2007)
Antifreeze proteins (AFPs) are ice-binding proteins that depress the freezing point of water in a non-colligative manner without a significant modification of the melting point. Found in the blood and tissues of some organisms (such as fish, insects, plants, and soil bacteria), AFPs play an important role in subzero temperature survival. Fish Type III AFP is present in members of the subclass Zoarcoidei. AFPIII are small 7-kDa—or 14-kDa tandem—globular proteins. In the present work, we study the behavior of several physical properties, such as the low-frequency dielectric permittivity spectrum, circular dichroism, and electrical conductivity of Fish Type III AFP solutions measured at different concentrations. The combination of the information obtained from these measurements could be explained through the formation of AFP molecular aggregates or, alternatively, by the existence of some other type of interparticle interactions. Thermal stability and electrooptical behavior, when proteins are dissolved in deuterated water, were also investigated.